Cluster modelling of MOF-5 and its application on gas storage - Sharma, Roshni; Gurung, Sristi; Adhikari, Kapil (Himalayan Physics, 2023)
MOF-5 exhibits unique characteristics for applications in gas storage particularly in the field of hydrogen storage. MOF-5 is a porous crystalline cubic structure formed by connecting a Zn4O inorganic moiety to benzene-1, 4-dicarboxylate (BDC), a bidentate ligand where, the Zn4O-cluster represents the central part of the structure. It can be an alternative to high pressure tanks and multistage compressor used in hydrogen storage. Using the cluster modelling approach, a thorough investigation of MOF-5 is provided. A density functional theory calculation was performed to examine the hydrogen storage potential in MOF-5. The geometry optimizations were carried out using the B3LYP functional together with the LanL2DZ/6-31G basis set. It is observed that the adsorption of hydrogen in MOF-5 cluster is physisorption and the hydrogen molecule is held in the core with the binding energy in the range 26-27 meV.